Histological Study of Rete Testis and Ductuli efferentes of Rabbit (Oryctolagus cuniculus) - Rakhmiyati, Rakhmiyati; Luthfi, Muhammad Jafar (Proceeding International Conference on Science and Engineering, 2019)
The testes produce sperm cells through the spermatogenesis process that occurs in the complex system ducts starting form seminiferous tubules to vas deferens. Testis has a very complex part to support sperm cell production. Sperm cells that have been formed through the process of spermatogenesis will move towards the lumen in the seminiferous tubules. Then the sperm cells will pass through the rete testis tissue, then to ductuli efferentes to arrive at the epididymis for the process of maturing sperm. Anatomical studies on seminiferous tubular tissue and epididymal organs have often been carried out, but there is still very little observation data on rete testis and ductuli efferentes in rabbits. The method used in this study was the paraffin method with hematoxylin-eosin (HE) staining. The observations showed that the structure of the testicular rete channels had thin walls compared to the seminifous tubule channels. Ductuli efferens is a channel between of rete testis and epididymis.